Frozen Convenience Noodles: Use of Ultrasound to Study the Influence of Preparation Methods on Their Rheological Parameters. Issue 5 (10th August 2017) - Daugelaite, Daiva; Strybulevych, Anatoliy; Norisuye, Tomohisa; Hatcher, David W.; Scanlon, Martin G.; Page, John H.
Abstract : Longitudinal ultrasonic waves were used to investigate effects of preparation and frozen storage time on the rheological properties of noodles. Noodles prepared with and without glucose oxidase (GOx) were flash frozen either immediately after production (raw), after blanching, or after being optimally cooked. From measurements of attenuation, phase velocity, loss and storage moduli ( M″ and M′ ), and tan δ L ( M″ / M′ ), it was found that raw noodles, prepared with or without GOx, were most similar overall to fresh noodles when stored frozen for one week. However, blanched noodles were closest to fresh noodles in terms of firmness, as measured by storage modulus, after one week of storage. Frozen storage for four weeks resulted in a significant loss in noodle quality. Stress relaxation measurements of Peleg's K 1 and K 2 parameters showed a significant effect of GOx addition on raw noodles after one week of frozen storage. As shown by K 1 and K 2 parameters, GOx addition delayed noodle texture deterioration associated with frozen aging for blanched and cooked treatments. The combined texture assessment of stress relaxation coupled with simultaneous ultrasonic measurements exhibits good potential for examining how formulation and pretreatment can mitigate the textural quality impairments associated with freezing of convenience noodles.